Integration of geography and sustainable tourism into the educational process - Mzarelua, Lana (The International tax journal, 2024)
The article presents the integration of tourism in the process of teaching geography. In the era of globalization, when the tourism industry is constantly developing and demand for it is growing, it is very important for any country to strengthen the tourism sector in the education system. More intensive teaching of tourism in schools increases the cultural and environmental awareness of students, expands career opportunities and develops global responsibility. This helps them become more trained professionals and thoughtful citizens of the world. Tourism education contributes to the achievement of sustainable development goals and a better understanding of economic, cultural and environmental issues. Therefore, it is necessary to integrate tourism topics into the process of teaching geography and develop knowledge in this area. It is also important to use effective training methods, such as cooperation with the tourism industry, which will contribute to the successful training of future specialists in the field of tourism.